Wisdom Epistemology in the Psalter : a Study of Psalms 1, 73, 90, and 107. - Kartje, John (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft., 2014)
There has been scant scholarship on the epistemology of the Psalter. This work presents a comparative epistemological analysis of the wisdom motifs in Psalms 1, 73, 90, and 107, selected on the basis of their epistemic content and canonical placement within the Psalter. An epistemological progression is found to develop across the canonical ordering of the four psalms, providing a helpful diagnostic for exploring the structure of the Psalter.